1995
DOI: 10.1128/jb.177.11.3176-3184.1995
|View full text |Cite
|
Sign up to set email alerts
|

A mutation that uncouples flagellum assembly from transcription alters the temporal pattern of flagellar gene expression in Caulobacter crescentus

Abstract: Caulobacter crescentus divides asymmetrically, forming two distinct cell types: a motile swarmer cell, with a single polar flagellum and chemotaxis machinery, and a sessile stalked cell. Transcription of flagellar genes is coordinated with cell cycle events, so that a new flagellum is synthesized and assembled at the swarmer pole of the predivisional cell before cell division is completed (reviewed in references 5 and 21). The flagellum consists of three major subassemblies (Fig.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(103 citation statements)
references
References 64 publications
4
99
0
Order By: Relevance
“…2A) and that all Class III flagellar genes can be transcribed in Class II mutant strains that also contain a bfa mutation (Mangan et al, 1995). The fljL flagellin gene is subject to this same control.…”
Section: Regulation Of Class II Genesmentioning
confidence: 98%
“…2A) and that all Class III flagellar genes can be transcribed in Class II mutant strains that also contain a bfa mutation (Mangan et al, 1995). The fljL flagellin gene is subject to this same control.…”
Section: Regulation Of Class II Genesmentioning
confidence: 98%
“…In Caulobacter, the molecular basis for the coupling of assembly of the £agellum with gene expression is not clear yet. Mutations that bypass the requirement of the ¢rst £agellar checkpoint (products of class II genes) for the transcription of class III genes and the £jL £agellin gene have been isolated and termed bfa (bypass of £agellar assembly) [38]. Both £jL and £jK are transcribed in bfa mutants but the corresponding £ag-ellin proteins are not synthesized, suggesting that both genes are also subject to post-transcriptional control [38].…”
Section: Polar Morphogenesismentioning
confidence: 99%
“…Mutations that bypass the requirement of the ¢rst £agellar checkpoint (products of class II genes) for the transcription of class III genes and the £jL £agellin gene have been isolated and termed bfa (bypass of £agellar assembly) [38]. Both £jL and £jK are transcribed in bfa mutants but the corresponding £ag-ellin proteins are not synthesized, suggesting that both genes are also subject to post-transcriptional control [38]. Both genes are also transcribed in all class III £agellar mutants tested but their mRNA is not translated in the absence of any of the known class III proteins [39].…”
Section: Polar Morphogenesismentioning
confidence: 99%
“…Flagellum synthesis requires nearly 50 genes, most of which are transcribed at a defined time in the cell cycle. Additionally, flagellar gene expression is influenced by a trans-acting regulatory hierarchy in which the expression and successful assembly of gene products that comprise early flagellar substructures are required for the expression of gene products incorporated later into the nascent flagellum (Newton et al, 1989;Xu et al, 1989;Ramakrishnan et al, 1994;Mangan et al, 1995). Epistasis experiments have demonstrated that this regulatory cascade consists of four hierarchical classes (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The cascade initiates with the temporal activation of the global transcription factor CtrA (class I), which, in turn, activates the transcription of the class II genes encoding the MS ring of the basal body, the flagellar switch and the flagellum-specific type III secretion system (TTSS) (Quon et al, 1996;Domian et al, 1997;Reisenauer et al, 1999). The assembly of this class IIencoded structure is required for the transcription of the flagellar class III and IV genes, encoding the basal bodyhook complex and the flagellin-containing filament, respectively (Newton et al, 1989;Xu et al, 1989;Ramakrishnan et al, 1994;Mangan et al, 1995). Thus, an assembly checkpoint functions to inhibit class III/IV gene expression until the class II-encoded structure is completed (Mangan et al, 1995;Muir & Gober, 2002).…”
Section: Introductionmentioning
confidence: 99%